P396 Ustekinumab Is A Promising Option For The Treatment Of Postoperative Recurrence Of Crohn's Disease. (30th January 2023) - Macaluso, F S; Grova, M; Mocciaro, F; Di Mitri, R; Privitera, A C; Distefano, M E; Vitello, A; Camilleri, S; Ferracane, C; Pluchino, D; Belluardo, N; Giangreco, E; et al.
Abstract: Background: Postoperative recurrence (POR) following ileocolonic resection is a major concern in patients with Crohn's disease (CD). The role of Ustekinumab (UST) as therapeutic option for the POR of CD is currently unknown Methods: All consecutive CD patients with a baseline colonoscopy at 6-12 months from ileocolonic resection showing POR with Rutgeerts score ≥ i2 who were treated with UST after the baseline colonoscopy, and with an available post-treatment endoscopy, were extracted from the cohort of the Sicilian Network for Inflammatory Bowel Diseases (SN-IBD). The primary outcome was endoscopic success, defined as reduction of at least one point of Rutgeerts score. The secondary outcome was clinical failure, assessed at the end of follow-up and defined in case of occurrence of one of the following: mild clinical relapse (Harvey-Bradshaw Index 5-7), clinically relevant relapse (Harvey-Bradshaw Index > 7), UST discontinuation due to adverse events, need for new resection. Results: Fifty-nine patients started UST for the management of POR. Five patients were excluded due to the absence of the baseline colonoscopy, 5 were excluded due to absent or mild POR (i.e. Rutgeerts score i0 or i1), and 5 patients were excluded due to short follow-up and the consequent absence of post-treatment colonoscopy. Finally, 44 patients were included (mean follow-up: 17.8 ± 8.4 months). The baseline postoperative colonoscopy showed an intermediate severity of recurrence (Rutgeerts score i2) in 25.0% of patients, and a severe recurrence (Rutgeerts score i3 or i4) in 75.0% of patients. Only 5 patients (11.4%) were naïve to biologics, while most had previous failure to one (61.4%), two (15.9%), or three (11.4%) biologics. The post-treatment colonoscopy was performed after a mean of 14.5 ± 5.5 months following initiation of UST. Endoscopic success was reported in 22 out of 44 (50.0%) patients, of whom 12 (27.3%) achieved a Rutgeerts score i0 or i1. None of these 22 patients with endoscopic success fulfilled the criteria for clinical failure. Clinical failure at the end of follow-up was reported in 12 out of 44 patients (27.3%); none of these 12 patients had achieved endoscopic success at post-treatment colonoscopy. At univariate Cox regression analysis, the number of previous biologics (HR 2.59 per-unit increase, 95% CI 1.33-5.03; p=0.005), previous surgery (HR 3.45, 95% CI 1.37-8.84; p=0.008), and need for steroids at baseline (HR 3.13, 95% CI 1.03-10.87; p=0.044) were associated with clinical failure at the end of follow-up. Conclusion: Ustekinumab could be a promising option for the treatment of POR of CD